2022
DOI: 10.3390/molecules27030728
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Responsive Photoluminescence and Elastic Properties of 1D Lead Halide Perovskites R- and S-(Methylbenzylamine)PbBr3

Abstract: Low-dimensional metal halide perovskites (MHPs) have received much attention due to their striking semiconducting properties tunable at a molecular level, which hold great potential in the development of next-generation optoelectronic devices. However, the insufficient understanding of their stimulus-responsiveness and elastic properties hinders future practical applications. Here, the thermally responsive emissions and elastic properties of one-dimensional lead halide perovskites R- and S-MBAPbBr3 (MBA+ = met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…[19][20][21][22][23] Therefore, OIMHs can provide a rich database for exploring promising candidates to serve as thermally responsive luminescent materials. [24][25][26][27][28][29] For example, zero-dimensional (0D) [PP 14 ] 2 [PbBr 4 ] (PP 14 = N-butyl-N-methylpiperidinium) has been reported to show a blue-emission, and this can be transformed to green-emitting [PP 14 ] 9 [PbBr 4 ] 2 [Pb 3 Br 11 ] after being heated at 100 1C for 5 min. 30 A copper-based material (Gua) 3 Cu 2 I 5 with blue emission at RT can transform to having yellow emission at 100 1C.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Therefore, OIMHs can provide a rich database for exploring promising candidates to serve as thermally responsive luminescent materials. [24][25][26][27][28][29] For example, zero-dimensional (0D) [PP 14 ] 2 [PbBr 4 ] (PP 14 = N-butyl-N-methylpiperidinium) has been reported to show a blue-emission, and this can be transformed to green-emitting [PP 14 ] 9 [PbBr 4 ] 2 [Pb 3 Br 11 ] after being heated at 100 1C for 5 min. 30 A copper-based material (Gua) 3 Cu 2 I 5 with blue emission at RT can transform to having yellow emission at 100 1C.…”
Section: Introductionmentioning
confidence: 99%
“…1,[11][12][13] For a given molecule-based piezoelectric, it is currently possible to predict its mechanical and piezoelectric properties using firstprinciples calculations of density functional theory (DFT) and density functional perturbation theory (DFPT), respectively. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Recently, these calculations have greatly improved the understanding of the origin of crystal mechanics and piezoelectricity for several piezoelectrics, such as (R-/S-(N-methylbenzylaminium))PbBr 3 , (Hmdabco)(NH 4 )X 3 (Hmdabco 2+ = 1-methyl-1,4-diazabicyclo-[2.2.2]octane-1,4-diium, X = Cl, Br, or I), and (benzyltrimethylammonium) 2 CoBr 4 . 19,20,25,26 Moreover, with the advantage of lower manufacturing costs when compared with conventional inorganic piezoelectric crystals, several molecule-based piezoelectric crystals have been assembled into piezoelectric generation devices for harvesting environmental vibrational energy to meet the requirements for self-energy supply in low-power devices.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27] Recently, these calculations have greatly improved the understanding of the origin of crystal mechanics and piezoelectricity for several piezoelectrics, such as (R-/S-(N-methylbenzylaminium))PbBr 3 , (Hmdabco)(NH 4 )X 3 (Hmdabco 2+ = 1-methyl-1,4-diazabicyclo-[2.2.2]octane-1,4-diium, X = Cl, Br, or I), and (benzyltrimethylammonium) 2 CoBr 4 . 19,20,25,26 Moreover, with the advantage of lower manufacturing costs when compared with conventional inorganic piezoelectric crystals, several molecule-based piezoelectric crystals have been assembled into piezoelectric generation devices for harvesting environmental vibrational energy to meet the requirements for self-energy supply in low-power devices. 11,12,22,23,26,[28][29][30][31][32][33][34][35][36][37][38] It was found that ferroelectrics, belonging to a class of piezoelectrics in which the direction of spontaneous polarization can be reversed by an applied electric field 13 and following a ferroelectric group-subgroup relationship during phase transitions, 39,40 generally have a higher piezoelectric effect than non-ferroelectric ones, and are thus more desired in seeking advanced piezoelectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid organic-inorganic perovskites (HOIPs) cover a diverse range of compositions and have achieved novel properties, such as dielectric transitions, ferroelectricities, and antiferroelectricities. With the development of hybrid materials, the ABX 3 -type HOIPs, which mimic the all-inorganic ABO 3 structure, have obtained much attention in physics and materials science . In ABX 3 -type HOIPs, the A metal ion is occupied by a midsized molecular cation, while the O ion is replaced by a monatomic and/or polyatomic anionic bridging ligand to form a normal cage-like perovskite structure. The organic components introduce additional functionalities and structural flexibility, and accordingly many members of the family show attractive characteristics, such as the excellent photovoltaic performance in the star compound (CH 3 NH 3 )­PbI 3 . …”
Section: Introductionmentioning
confidence: 99%